Dickkopf-related protein-1 inhibition attenuates amyloid-beta pathology associated to Alzheimer's disease. (December 2020) - Menet, Romain; Bourassa, Philippe; Calon, Frédéric; ElAli, Ayman
Abstract: Alzheimer's disease (AD) constitutes the leading cause of dementia worldwide. It is associated to amyloid-β (Aβ) aggregation and tau hyper-phosphorylation, accompanied by a progressive cognitive decline. Evidence suggests that the canonical Wnt pathway is deregulated in AD. Pathway activity is mediated by β-catenin stabilization in the cytosol, and subsequent translocation to the nucleus to regulate the expression of several genes implicated in brain homeostasis and functioning. It was recently proposed that Dickkopf-related protein-1 (DKK1), an endogenous antagonist of the pathway, might be implicated in AD pathogenesis. Here, we hypothesized that canonical Wnt pathway deactivation associated to DKK1 induction contributes to late-onset AD pathogenesis, and thus DKK1 neutralization could attenuate AD pathology. For this purpose, human post-mortem AD brain samples were used to assess pathway activity, and aged APPswe/PS1 mice were used to investigate DKK1 in late-onset AD-like pathology and therapy. Our findings indicate that β-catenin levels progressively decrease in the brain of AD patients, correlating with the duration of symptoms. Next, we found that Aβ pathology in APPswe/PS1 mediates DKK1 induction in the brain. Pharmacological neutralization of DKK1's biological activity in APPswe/PS1 mice restores pathway activity by stabilizing β-catenin, attenuates Aβ pathology, and ameliorates the memory of mice. Attenuation of AD-like pathology upon DKK1 inhibition is accompanied by a reduced protein expression of beta-site amyloid precursor protein (APP) cleaving enzyme-1 (BACE1). Moreover, DKK1 inhibition enhances vascular density, promotes blood-brain barrier (BBB) integrity by increasing claudin 5, glucose transporter-1 (GLUT1), and ATP-binding cassette sub-family B member-1 (ABCB1) protein expression, as well as ameliorates synaptic plasticity by increasing brain-derived neurotrophic factor (BDNF), and postsynaptic density protein-95 (PSD-95) protein expression. DKK1 conditional induction reduces claudin 5, abcb1, and psd- 95 mRNA expression, validating its inhibition effects. Our results indicate that neutralization of DKK1's biological activity attenuates AD-like pathology by restoring canonical Wnt pathway activity. Highlights: Canonical Wnt pathway is deactivated in the brain of AD patients dependently upon the duration of symptoms. Canonical Wnt pathway deactivation is exacerbated in AD patients carrying ApoEε4. Induction DKK1 in the brain is associated to Aβ pathology. DKK1 neutralization attenuates AD-like pathology by restoring canonical Wnt pathway activity.